A STUDY OF THE EFFECTS OF LIFESTYLE CHANGES ON URBAN TRIP GENERATION WITH AN APPROACH TO FUTURES STUDIES: A CASE STUDY OF TEHRAN REGION 6 - Rastad Borujeni, Marzieh; Shafiee-Masuleh, Seyedeh-Samira; Shafiee Masouleh, Seyed Reza (Journal of Regional and City Planning, 2019)
This research is a descriptive analytical study. The goal was to identify the key factors that affect lifestyle changes and urban trip generation. To achieve this goal, we used two components (pattern, value), 20 criteria (social, economic, cultural, psychological, political, etc.), and 56 variables. For data analysis, the Delphi method, cross-impact analysis and MICMAC were used. The results showed that 25 factors were key factors affecting urban lifestyle changes and urban trip generation. These factors, in order of priority, were: increasing income level of people; more welcoming to urban residents from well-kept homes and high-quality residential neighborhoods; changing role of streets for a new type of recreational trips apart from serving traffic;increasing number of young and adolescents in the region; increasing daily, monthly, seasonal and annual purchases from large retail stores and luxury shopping malls away from downtown; increasing residency of people in new and high-quality urban areas away from the central areas of the city; increasing rate of apartment living and people?s preference to stay in apartments rather than single-family houses; increasing number of single people; increasing non work-related trips, etc. Moreover, the results showed that changes in patterns lead to changes in values and, ultimately, lifestyle changes and increased urban trip generation.Abstrak. Penelitian ini adalah penelitian deskriptif analitik. Tujuan dari penelitian ini adalah untuk mengidentifikasi faktor-faktor kunci yang mempengaruhi perubahan gaya hidup dan generasi perjalanan perkotaan. Untuk mencapai tujuan ini, kami menggunakan dua komponen (pola, nilai), 20 kriteria (sosial, ekonomi, budaya, psikologis, politik, dan lain-lain), dan 56 variabel. Untuk analisis data, digunakan metode Delphi, analisis dampak silang dan MICMAC. Hasil penelitian menunjukkan ada 25 faktor yang merupakan faktor kunci yang mempengaruhi perubahan gaya hidup perkotaan dan generasi perjalanan perkotaan. Faktor-faktor ini, dalam urutan prioritas, adalah: peningkatan tingkat pendapatan masyarakat, peningkatan sambutan penduduk kota yang berasal dari rumah yang terawat baik dan lingkungan perumahan yang berkualitas tinggi, perubahan peran jalan untuk perjalanan rekreasi jenis baru selain melayani lalu lintas, perluasan kelompok usia muda (kenaikan jumlah kaum muda dan remaja) di wilayah tersebut, peningkatan belanja harian, bulanan, musiman dan tahunan dari toko ritel besar dan pusat perbelanjaan mewah yang jauh dari pusat kota, peningkatan jumlah penduduk di daerah perkotaan baru dan berkualitas tinggi yang jauh dari pusat kota, kenaikan tingkat kehidupan di apartemen dan preferensi orang untuk tinggal di apartemen daripada di rumah keluarga tunggal, penambahan jumlah orang lajang, kenaikan perjalanan yang tidak berhubungan dengan pekerjaan, dan lain-lain. Selain itu, hasil menunjukkan bahwa perubahan pola tersebut menyebabkan perubahan nilai dan, pada akhirnya, perubahan gaya hidup dan peningkatan generasi perjalanan perkotaan.Kata kunci. Gaya hidup, generasi perjalanan perkotaan, studi masa depan, metode Delphi.